Spatial And Temporal Variation Of Water Quality And Phytoplankton In The Constructed Wetlands In Universiti Sains Malaysia - Shaharuddin, Syafiq (2019)
Constructed wetlands are built to improve water quality while serving as an alternative sustainable habitat for aquatic life. In Malaysia, constructed wetlands are designed according to the guideline for Urban Stormwater Management Manual for Malaysia (MSMA 2nd ed.) 2012. This study shall evaluate the spatial and temporal performance of the constructed wetland design as stipulated by MSMA through an assessment of water quality and phytoplankton growth, which acts as a biodiversity indicator. The assessment included a 13-month sampling period starting from November 2014 until November 2015 whereby the phytoplankton abundance in a constructed wetland was correlated with the water quality parameters. The constructed wetland consists of three main zones, namely the forebay, macrophytes and micropool zones. The microphyte zone showed the highest average measurement of pollutants as opposed to the other zones. The WQI was chosen as it can group the 6 main parameters into one reference value, which will be further referred to the quality class. The highest WQI value (good water quality) was obtained from the micropool zone at 82.67 (Class II) while the lowest WQI value was collected from the macrophytes zone with 65.37 (Class III). The pollutant reduction was effective and high from the inlet macrophyte to the outlet micropool, with the percentage reduction of TSS at 76%, TN at 35% and orthophosphate at 56% compared to the reduction from the inlet forebay to the outlet micropool. A total of 20 phytoplankton species from 5 different algal phyla were identified in the constructed wetland. The dominant group was Chlorophyta group while the species of Westella botryoides and Coelastrum microporum were found to be dominant in the constructed wetland. The changes of total phytoplankton abundance were observed from 15,490.2 cell m-3 ± 586 in the macrophyte zone, and reduced in the micropool zone to 9,599.3 cell m-3 ± 386. However there was a slight difference in the total abundance of phytoplankton during dry and wet periods, at 15,765.2 cell m-3 ± 567 and 14,391.3 cell m-3 ± 599, with the dry season recording more than the wet season. The total abundance of phytoplankton was low compared to other references, thus this constructed wetland can be classified as mesotrophic based on the trophic class. Upon the correlation analysis using Pearson correlation and PCA, the total abundance of phytoplankton was correlated to the orthophosphate concentration. The orthophosphate concentration showed significance correlation with the phytoplankton composition, with the high R2 value between 0.7 to 0.9. At the same time, the design of the macrophyte zone influences the phytoplankton distribution and abundance. Hence, this zone indicated an increase in the abundance of phytoplankton, which was most likely influenced by the water quality condition. The correlation change from WQI, orthophosphate and phytoplankton abundance showed that the phytoplankton was a good biological indicator, not only for water quality, but also to gauge the biodiversity level and sustainability of habitat.